The effect of mental fatigue on sport-specific endurance and technical performances - Filipas, L. (British Journal of Sports Medicine, 2021)
Acute mental fatigue is defined as a psychobiological state that may arise during or after prolonged cognitive activities. While the effects of mental fatigue on cognitive performance have been widely investigated, the interest of researchers in investigating a potential impact of mental fatigue on physical performance remains a hot topic. Despite some studies showing that mental fatigue appears to impair sport performance through an increased rating of perceived exertion (RPE) for the same physical effort, the scientific comprehension of this topic is still limited. Therefore, the aim of this PhD was to investigate the effects of mental fatigue on sport-specific endurance and technical performances. In addition, the project sought to clarify whether mental fatigue tolerance could be trainable or not.